Dr. Klaus Rodrigues de Oliveira — Deep Plane Facelift — Belo Horizonte - Rodrigues de Oliveira, Klaus (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Klaus Rodrigues de Oliveira, practicing in Belo Horizonte, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003178; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; belo horizonte